2017
DOI: 10.1016/j.jpsychires.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural activations are related to body-shape, anxiety, and outcomes in adolescent anorexia nervosa

Abstract: Anorexia nervosa (AN) is an illness that frequently begins during adolescence and involves weight loss. Two groups of adolescent girls (AN-A, weight-recovered following AN) and (HC-A, healthy comparison) completed a functional magnetic resonance imaging task involving social evaluations, allowing comparison of neural activations during self-evaluations, friend-evaluations, and perspective-taking self-evaluations. Although the two groups were not different in their whole-brain activations, anxiety and body shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…First, they deliver evidence suggestive of a partial normalization of neural processes subserving DD, after short-term weight restoration. The longitudinal changes in DMN activation observed here during performance of a DD task dovetail with previous findings of alterations in these regions in individuals with AN, both at rest [66,67] and during other self-relevant decision-making tasks [69][70][71][72]. Although supplementary analyses of functional connectivity between the identified DMN regions and task-positive FPN regions did not detect significant longitudinal differences, future-focused analysis of antagonism between task-positive and task-negative networks [83] might provide a unique window on brain function and dysfunction in AN [84][85][86].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First, they deliver evidence suggestive of a partial normalization of neural processes subserving DD, after short-term weight restoration. The longitudinal changes in DMN activation observed here during performance of a DD task dovetail with previous findings of alterations in these regions in individuals with AN, both at rest [66,67] and during other self-relevant decision-making tasks [69][70][71][72]. Although supplementary analyses of functional connectivity between the identified DMN regions and task-positive FPN regions did not detect significant longitudinal differences, future-focused analysis of antagonism between task-positive and task-negative networks [83] might provide a unique window on brain function and dysfunction in AN [84][85][86].…”
Section: Discussionsupporting
confidence: 88%
“…However, suggesting that normalization was only partial and regionally specific, dACC activation generally increased in acAN-TP2, but still did not exhibit a normal response on difficult vs. easy trials [59], as observed previously in both HC and recAN [20,40]. Second, while aberrant DMN function has been repeatedly described in AN, both at rest [66,67] and during disorder-relevant stimulation [68][69][70][71][72], the apparent longitudinal improvement observed here in a task that recruited the FPN, suggests that the abnormalities might be primarily associated with the underweight state and might not constitute a trait variable of the disorder. Based on our previous findings of consistently faster decision-making and altered neural efficiency in the FPN during DD in acAN compared to HC [40], we speculate that the relative attenuation of DMN deactivation in acAN-T2 might reflect a relaxation of excessive self-control over the course of treatment or a shift from more habitual to intentional execution of self-control.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…During a self-and-other social evaluation task, anxiety and body shape concerns correlated inversely in participants with AN compared with controls, with prefrontal and cingulate brain response, implicating those regions. 90 Gentle touch or intimate visual stimuli were rated less pleasant in participants with AN compared with controls, and were associated with lower caudate or parietal activity, suggesting reduced reward experience. 91,92…”
Section: Social Function and Stressmentioning
confidence: 90%
“…Additionally, this region shows significant grey matter loss in AN, and it might particularly also be susceptible to the effects of AN in the long run [53,61,62]. Xu et al [63] recently pointed to the importance of the precuneus and the medial prefrontal cortex during social evaluations in AN, including a possible predictive value.…”
Section: Discussionmentioning
confidence: 99%